Emergence of IncHI2 Plasmids With Mobilized Colistin Resistance (mcr)-9 Gene in ESBL-Producing, Multidrug-Resistant Salmonella Typhimurium and Its Monophasic Variant ST34 From Food-Producing Animals in Italy - Diaconu, Elena Lavinia; Alba, Patricia; Feltrin, Fabiola; Di Matteo, Paola; Iurescia, Manuela; Chelli, Eleonora; Donati, Valentina; Marani, Ilaria; Giacomi, Angelo; Franco, Alessia; Carfora, Virginia (Frontiers in Microbiology, 2021)
A collection of 177 genomes of S. Typhimurium and its monophasic variant isolated in 2014-2019 from Italian poultry/livestock (n=165) and foodstuff (n=12), previously screened for antimicrobial susceptibility and assigned to ST34 and single-locus variants, were in-depth studied to check the presence of the novel mcr-9 gene and to investigate their genetic relatedness by whole genome sequencing (WGS). The study of accessory resistance genes revealed the presence of mcr-9.1 in eleven ST34 isolates, displaying elevated colistin MIC values up to 2 mg/L and also a multidrug resistant (MDR) profile towards up to seven antimicrobial classes with five of them being also ESBL-producers (blaSHV-12 type), mediated by the corresponding AMR accessory genes. All mcr-9 positive isolates harbored IncHI2-ST1 plasmids. From the results of Mash analysis performed on all 177 genomes, the eleven mcr-9 positive isolates fell together in the same subcluster and were all closely related. This subcluster included also two mcr-9 negative isolates and other eight mcr-9 negative ST34 isolates were present within the same parental branch. All the 21 isolates within this branch presented an IncHI2/2A plasmid and a similar MDR genes pattern. In three representative mcr-9 positive isolates, mcr-9 was demonstrated to be located on different IncHI2/IncHI2A large-size (∼277-297 kb) plasmids, using a combined Illumina-Oxford Nanopore WGS approach. These plasmids were also compared by BLAST analysis with publicly available IncHI2 plasmid sequences harboring mcr-9. In our plasmids, mcr-9 was located in a ∼30 kb region lacking different genetic elements of the typical core structure of mcr-9 cassettes. In this region were also identified different genes involved in heavy metals metabolism. Our results underline how genomics and WGS- based surveillance are increasingly indispensable to achieve better insights into the genetic environment and features of plasmid-mediated AMR, as in the case of such IncHI2 plasmids harboring other MDR genes beside mcr-9, that can be transferred horizontally also to other major Salmonella serovars spreading along the food chain.